Magnetic Water Effect on Concrete Properties of Canal Lining - Hoobi Irzooki, Raad; Saleem Khazaal, Ammar; Imad Mohammed, Zaid (International Journal of Engineering and Technology, 2018)
The present research investigated the magnetic field effect on the properties of tap water and the magnetic water effect on some properties of the concrete used for irrigation canal lining, so, for this purpose, the absorption and seepage features of concrete will be studied. The magnetic water was obtained by passing the tap water through magnetized devices with three different intensities (3000, 5000, and 7000) Gauss for 120 minutes. Some properties of magnetized water such as surface tension, viscosity, conductivity, TDS, and pH were studied. The results show that the surface tension, viscosity and electric conductivity of treated water with three different magnetization intensities were decreased about (19-22)%, (4-5)% and (6-8)% respectively as compared with results of the tap water. Also, the results show that pH was increased about (8-10)%. The magnetized water effect on the properties of concrete like compressive strength, slump, absorption, and seepage were studied. The results show that using the magnetized water (with three different intensities) instead of the tap water increased the compressive strength of concrete between (3-17)% for age of 28 days, and increased the slump between (5-13)mm. This leads to the possibility of increasing the water-cement ratio, which is, means decreasing the cost of concrete at a specified value of compressive strength. Also, the results show that the absorption and seepage were decreased about (1-9.5) % and (2-20)% respectively.Â Â